Chunk-level request-grant-transfer mode for QoE-sensitive video delivery in CDN - Shen, Gengbiao; Li, Qing; Jiang, Yong; Sinnott, Richard; Lin, Dong; Guo, Zehua; Wang, Yi (Proceedings of the International Symposium on Quality of Service, 2019)
Remote Direct Memory Access (RDMA) can be deployed in Content Delivery Networks (CDN) Points of Presence (PoPs) to avoid the high CPU overheads caused by traditional TCP/IP stacks. However, RDMA cannot surmount the drawbacks of the window-based conservative of TCP and is insensitive to Quality of Experience (QoE). Moreover, the requirement of lossless networks hinders the widespread application of RDMA. In this paper, we introduce the parallel multipoint-to-multipoint Request-Grant-Transfer (RGT) mode into RDMA to solve the aforementioned problems. Compared with traditional RGT mode, our scheme supports parallel Dynamic Adaptive Streaming over HTTP (DASH) chunk delivery, thereby improving throughput and reducing initial delays. We differentiate the importance of DASH chunks according to QoE-related properties. In this way, we reduce the response time of specific DASH chunks. We provide an efficient approach to select the optimal number of requests for partially traversing pending requests to reduce the overheads of Request stages. We perform comprehensive experiments to demonstrate that our scheme improves the throughput of CDN PoPs and enhances client QoE.